The Influence of Marketing Mix (7P) on Patient Satisfaction in Hospitals: A Literature Review - Yusron, Ahmad; Rohmah, Nur; Ningsih, Riyan (Mulawarman International Conference on Tropical Public Health, 2025)
Healthcare services in hospitals are rapidly developing. To cope with these changes, hospitals are required to implement optimal strategies to compete and adapt. Hospital marketing is becoming increasingly competitive worldwide. Marketing mix strategy is considered one of the core concepts of marketing theory. This literature review aims to analyze the effect of the marketing mix on patient satisfaction in various hospitals. The research method used in this study is a Systematic Literature Review (SLR). Search from google scholar, PubMed, google.com, Portal Garuda, with search keywords "marketing mix", "patient satisfaction" and “hospital". Published articles from 2019 to 2024. Reference From the 70 articles obtained, then the articles used were 8 articles that met the inclusion criteria. Overall, the results of this literature review indicate that the implementation of a comprehensive marketing mix strategy plays an important role in improving "patient satisfaction" and indicates that "patient satisfaction" can be optimized through integrated management of "marketing mix" components. All articles studied show the results of the influence of the marketing mix (product, price, place, promotion, people, process, physical evidence) on patient satisfaction  in hospitals.